Disentangling euro area portfolios: New evidence on cross-border securities holdings - Linda Rousová; Antonio Rodríguez Caloca (European Central Bank (ECB), 2018)
This paper presents a detailed set of new, quantity-based indicators of financial integration in the euro area. The indicators are based on granular data from securities holdings statistics and help us disentangle the main drivers of the portfolio changes observed since the financial crisis. Three key developments since the crisis stand out. First, we find that financial integration in equity is less than that in the debt market, although the equity market was the main contributor to the partial recovery in financial integration observed since mid-2012. Second, we observe a gradual shift in cross-border investment activity from the banking sector towards other non-bank financial entities. In particular, our results show that euro area banks significantly decreased their investment in debt securities issued by banks in other euro area countries and that this decrease explains around 55% of the decline in financial integration in the debt market observed since the crisis. Finally, we find that the sharp decrease in financial integration between 2009 and 2012 was mainly driven by foreign investor flight from government debt securities, a trend that has since reversed.
Keywords: F36; G1; G10; G15; 330; securities holdings statistics; security-by-security data; micro-data; financial integration; quantity-based indicators; securities; international financial markets